A literature review on possible industrial applications of fatty acid: article - A.Rahman, S.N; Hanipah, S.H; Hashim, M.A (2017)
The purpose of this research are to find out the possible industrial applications of fatty acid, especially in Malaysia. To get the result, it is required to get the latest information on the production of fatty acid in Malaysia, the sources of fatty acids, he procuder of fatty acid and the industries that use fatty acid as raw material of products. Since local Industries grow rapidly, it is suggested to get the data on the last 5 years. In this research, it is required to know either Malaysia produce its own fatty acids or import it from other country. For the purpose of study, it is required to know the annual production of fatty acids. Also, this requires knowing from which country did Malaysia import or export its fatty acids. As results, fatty acid was found being used in pharmaceutical, soup and detergents and many more industrial applications. Fatty acid may come from animal such as pork, chicken and fish and come from plants such as palm oil and coconut oil.